Measuring changes in background dissolved gases to evaluate multi-component gas dissolution: Laboratory experiments and implications for stray gas monitoring - Madeline M. Calvert; Mitchell A. Davidson; Ariel Nunez Garcia; Kevin G. Mumford (Advances in Water Resources, 2024)

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Optimising the selection of outcomes for healthy ageing trials: a mixed methods study - Muslim Abbas Syed; Olalekan Lee Aiyegbusi; Eliot Marston; Janet M. Lord; Harriet Teare; Melanie Calvert (GeroScience, 2022)
Advancing age is associated with chronic diseases which are the largest cause of death and disability in developed countries. With increasing life expectancy and an ageing population, there is a need to conduct trials to extend healthy ageing, including targeting biological ageing processes, and prevent ageing-related diseases. The main objectives of the study are as follows: (i) to review outcome measures utilised in healthy ageing trials focusing on pharmacological therapies, nutritional supplements and medical devices; (ii) to summarise the views of key stakeholders on outcome selection for healthy ageing trials. An analysis of records from the Clinicaltrials.gov database pertaining to healthy ageing trials from inception to May 2022 was conducted. In addition, the findings of a workshop attended by key stakeholders at the 2022 annual UKSPINE conference were qualitatively analysed. Substantial heterogeneity was found in the interventions evaluated and the outcomes utilised by the included studies. Recruitment of participants with diverse backgrounds and the confounding effects of multi-morbidity in older adults were identified as the main challenges of measuring outcomes in healthy ageing trials by the workshop participants. The development of a core outcome set for healthy ageing trials can aid comparability across interventions and within different settings. The workshop provided an important platform to garner a range of perspectives on the challenges with measuring outcomes in this setting. It is critical to initiate such discussions to progress this field and provide practical answers to how healthy ageing trials are designed and structured in the future.

Compaction- and Shear-Induced Well Deformation in Tyra: Geomechanics for Impact on Production - P. M. T. M. Schutjens; P. Fokker; U. B. B. Rai; J. Kandpal; M. V. Cid Alfaro; N. D. Hummel; R. Yuan; F. Klever; S. De Gennaro; J. Vaibav; F. Bourgeois; M. Calvert; et al. (Rock Mechanics and Rock Engineering, 2019)

Multi-scenario Geomechanical Modeling for Investigating Well Deformation in the Deep Overburden Over a Compacting Reservoir in the North Sea - R. S. Yuan; M. A. Calvert; P. M. T. M. Schutjens; F. G. Bourgeois (Rock Mechanics and Rock Engineering, 2019)

Acute Pesticide-Related Illness Among Farmworkers: Barriers to Reporting to Public Health Authorities - Joanne Bonnar Prado; Prakash R. Mulay; Edward J. Kasner; Heidi K. Bojes; Geoffrey M. Calvert (Journal of Agromedicine, 2017)

Acute Illness Associated with Exposure to a New Soil Fumigant Containing Dimethyl Disulfide—Hillsborough County, Florida, 2014 - Prakash R. Mulay; Philip Cavicchia; Sharon M. Watkins; Antonio Tovar-Aguilar; Michael Wiese; Geoffrey M. Calvert (Journal of Agromedicine, 2016)

Prevalence of Musculoskeletal Symptoms Among Agricultural Workers in the United States: An Analysis of the National Health Interview Survey, 2004–2008 - Soo-Jeong Lee; Sangwoo Tak; Toni Alterman; Geoffrey M. Calvert (Journal of Agromedicine, 2014)

Severe Acute Illness in a Toddler Exposed to Multiple Agricultural Pesticides and an Insect Repellent - Jennifer S. Sievert; Barbara F. Morrissey; Geoffrey M. Calvert (Journal of Agromedicine, 2013)

Promoting and Protecting Worker Health and Safety in the Republic of Korea Agricultural Sector - Geoffrey M. Calvert; Kyungsuk Lee; Sangchul Roh; Kermit G. Davis; SangWoo Tak (Journal of Agromedicine, 2012)

Variation in songbird migratory behavior offers clues about adaptability to environmental change - Anna M. Calvert; Stuart A. Mackenzie; Joanna Mills Flemming; Philip D. Taylor; Sandra J. Walde (Oecologia, 2012)

Cross‐scale environmental influences on migratory stopover behaviour - ANNA M. CALVERT; PHILIP D. TAYLOR; SANDRA WALDE (Global Change Biology, 2009)
Migratory species may be especially sensitive to climate change because their lifecycles are affected by dynamic ecological processes operating at global spatial scales. Insight into environmental effects upon en route decisions by migrants can therefore be a critical first step toward assessing their vulnerability to future climatic shifts. We extracted behaviour‐related parameters from a recent formulation of multistate mark–recapture models, and used them to evaluate the importance of variation in local weather and broad‐scale climate to decisions made by autumn passerine migrants at a coastal stopover site in Atlantic Canada. We found dramatic interannual fluctuations in the proportion of migrants that were transient (departing within a day of arrival), with annual average values ranging from 24% to 96% over the years 1996–2007. However, the relationships of stopover behaviour (transience and departure probability) to local weather (wind and precipitation) and to regional climatic fluctuations were similar across three distinct species groups and for birds of different fuel‐loads, indicating the potential for both immediate (day‐to‐day) and long‐term environmental influences (spanning several seasons). This cross‐scale approach contributes valuable information toward the conservation of migrants in the face of a changing climate by (i) quantifying environmental influences on stopover behaviour in broad temporal and geographic contexts, and (ii) demonstrating largely parallel interannual variation in stopover site‐use among birds with contrasting migratory timing and strategies.

Dissolution characteristics of central Florida phosphate rock in an acidic sandy soil - Z. L. He; H. Yao; D. V. Calvert; P. J. Stoffella; X. E. Yang; G. Chen; G. M. Lloyd (Plant and Soil, 2005)

Three-dimensional mapping of a landslide using a multi-geophysical approach: the Quesnel Forks landslide - A. Bichler; P. Bobrowsky; M. Best; M. Douma; J. Hunter; T. Calvert; R. Burns (Landslides, 2004)

Hemifacial microsomia: progress in understanding the genetic basis of a complex malformation syndrome - D. Kelberman; J. Tyson; D. Chandler; A. McInerney; J. Slee; D. Albert; A. Aymat; M. Botma; M. Calvert; J. Goldblatt; E. Haan; N. Laing; et al. (Human Genetics, 2001)

Effect of deletion and the site of insertion in double copy anti-tat retroviral vectors: viral titres and production of anti-tat mRNA - J. M. Carr; J. K. Calvert; R. Kumar; C. J. Burrell; P. Li (Archives of Virology, 2001)

Genetic structure of the world’s polar bear populations - D. Paetkau; S. C. Amstrup; E. W. Born; W. Calvert; A. E. Derocher; G. W. Garner; F. Messier; I. Stirling; M. K. Taylor; Ø. Wiig; C. Strobeck (Molecular Ecology, 1999)
We studied genetic structure in polar bear ( Ursus maritimus ) populations by typing a sample of 473 individuals spanning the species distribution at 16 highly variable microsatellite loci. No genetic discontinuities were found that would be consistent with evolutionarily significant periods of isolation between groups. Direct comparison of movement data and genetic data from the Canadian Arctic revealed a highly significant correlation. Genetic data generally supported existing population (management unit) designations, although there were two cases where genetic data failed to differentiate between pairs of populations previously resolved by movement data. A sharp contrast was found between the minimal genetic structure observed among populations surrounding the polar basin and the presence of several marked genetic discontinuities in the Canadian Arctic. The discontinuities in the Canadian Arctic caused the appearance of four genetic clusters of polar bear populations. These clusters vary in total estimated population size from 100 to over 10 000, and the smallest may merit a relatively conservative management strategy in consideration of its apparent isolation. We suggest that the observed pattern of genetic discontinuities has developed in response to differences in the seasonal distribution and pattern of sea ice habitat and the effects of these differences on the distribution and abundance of seals.

AGE STRUCTURE AND REPRODUCTIVE RATES OF RINGED SEALS ( PHOCA HISPIDA ) ON THE NORTHWESTERN COAST OF HUDSON BAY IN 1991 AND 1992 1 - M. Holst; Ian Stirling; W. Calvert (Marine Mammal Science, 1999)

Comparison of Colombian and Costa Rican Strains of Rice Hoja Blanca Tenuivirus - Joachim R. De Miranda; Bertha-Cecilia Ramirez; Miguel Mun~oz; Ivan Lozano; Ray Wu; Anne-Lise Haenni; Ana M. Espinoza; Lee A. Calvert (Virus Genes, 1997)